2017
DOI: 10.1002/ijc.30595
|View full text |Cite
|
Sign up to set email alerts
|

The multifaceted role of extracellular vesicles in metastasis: Priming the soil for seeding

Abstract: Extracellular vesicles (EVs), including exosomes, play a key role in inter and intracellular communication, promoting the proliferation and invasion of recipient cells to support tumor growth and metastasis. Metastasis comprises multiple steps that first include the detachment of tumor cells through epithelial to mesenchymal transition (EMT), allowing the physical dissemination to distant organs. Thereafter, cancer-derived exosomes are still critical components for preparing the tumor microenvironment by (i) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 124 publications
(237 reference statements)
0
58
0
Order By: Relevance
“…Exosomes have emerged as regulators of intercellular and intracellular communication and can “tailor” the premetastatic niche for engraftment of cancer cells . Interestingly, the 4T1 model displayed significantly increased circulating blood exosomes at D3, simultaneous with the first evidence of lung metastasis, suggesting its active role in lung metastasis establishment . However, we did not find any modulation in exosome levels in MDA‐MB‐231‐Luc.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes have emerged as regulators of intercellular and intracellular communication and can “tailor” the premetastatic niche for engraftment of cancer cells . Interestingly, the 4T1 model displayed significantly increased circulating blood exosomes at D3, simultaneous with the first evidence of lung metastasis, suggesting its active role in lung metastasis establishment . However, we did not find any modulation in exosome levels in MDA‐MB‐231‐Luc.…”
Section: Discussionmentioning
confidence: 99%
“…By intercellular transfer of surface proteins, donor cancer cells can modulate the activity of recipient cells and play important roles in tumorigenesis, growth, metastasis and even drug resistance. Moreover, cancer cells using intercellular transfer of cell‐surface proteins also play critical roles in re‐shaping the tumor microenvironment to support their expansion and metastatic activity, as well as dampen antitumor immune responses . In this context, a recent study by Hamieh et al .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cancer cells using intercellular transfer of cell-surface proteins also play critical roles in re-shaping the tumor microenvironment to support their expansion and metastatic activity, as well as dampen antitumor immune responses. 15,16 In this context, a recent study by Hamieh et al 17 revealed that both CD19 and CD22 expressed on NALM6 acute lymphoblastic leukaemia cells could be transferred to chimeric antigen receptor (CAR)-T cells through the process of trogocytosis. Consequently, the density of the target molecules CD19 and CD22 was decreased on the tumor cells, and the T-cell killing activity was abated by the fratricide and exhaustion of the T cells with molecules acquired target by trogocytosis by CAR-T cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is also noteworthy that EVs and their content can serve as biomarkers for cancer . Given that there are changes in EV content that could mediate their ability to induce drug resistance when transferred between cells, it is logical that these changes could also serve as a biomarker for the presence of tumors that are either resistant to specific drugs or harbor the capacity to transfer resistance .…”
Section: Perspective and Future Directionsmentioning
confidence: 99%